2015
DOI: 10.18632/oncotarget.6089
|View full text |Cite
|
Sign up to set email alerts
|

Intra-tumor AvidinOX allows efficacy of low dose systemic biotinylated Cetuximab in a model of head and neck cancer

Abstract: For locally advanced and metastatic head and neck squamous cell carcinoma (HNSCC), the current clinical use of Cetuximab in chemo/radiotherapy protocols is often associated to severe systemic toxicity. Here we report in vitro data in human FaDu pharynx SCC cells, showing that inactive concentrations of biotinylated Cetuximab (bCet) become active upon anchorage to AvidinOX on the surface of tumor cells. AvidinOX-anchored bCet induces apoptosis and DNA damage as well as specific inhibition of signaling, degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…The present work confirms and extends data from a previous study that showed the efficacy of using AvidinOX in mice bearing subcutaneous tumor xenografts treated with systemic low doses of bCet (13). The current study demonstrated that this therapeutic approach is also effective in an orthotopic model (tongue xenograft) and that efficacy can be further improved by adding a low dose of cisplatin to the treatment protocol.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The present work confirms and extends data from a previous study that showed the efficacy of using AvidinOX in mice bearing subcutaneous tumor xenografts treated with systemic low doses of bCet (13). The current study demonstrated that this therapeutic approach is also effective in an orthotopic model (tongue xenograft) and that efficacy can be further improved by adding a low dose of cisplatin to the treatment protocol.…”
Section: Discussionsupporting
confidence: 90%
“…1A confirm results obtained in a previous study using FaDu subcutaneous tumor xenografts, which demonstrated the anti-tumor efficacy of low dose bCet in AvidinOX-treated tumors. These results are supported by in vitro data indicating that AvidinOX-anchored bCet causes induction of EGFR degradation, inhibition of EGFR nuclear translocation and downstream signaling, plus upregulation of pro-apoptotic and cell damage markers (13). In the current study, the tumor growth inhibition of bCet was further improved by additional administration of low dose cisplatin; in fact, tumor masses treated with AvidinOX in mice receiving low doses of intraperitoneal bCet and cisplatin were significantly smaller than the tumor masses of mice treated with AvidinOX+bCet, or bCet+cisplatin.…”
Section: Tumor Growth Inhibition Mice With Human Fadu Tonguesupporting
confidence: 62%
See 3 more Smart Citations